On the Fortieth Anniversary of the Miranda Case: Why We Needed It, How We Got It--And What Happened to It - Kamisar, Yale (2007)
Last year (the year I gave the talk on which this article is based) marked the fortieth anniversary of Miranda v. Arizona,' one of the most praised, most maligned-and probably one of the most misunderstood-Supreme Court cases in American history. It is difficult, if not impossible, to evaluate Miranda without looking back at the test for the admissibility of confessions that preceded it